Optimization of roughage to concentrate ratio in sweet sorghum bagasse based complete ration for efficient microbial biomass production in sheep using in vitro gas technique - Kumari, N.N.; Reddy, Y.R.; Blümmel, Michael; Monika, T. (2012)
An in vitro study was conducted to evaluate the optimum roughage to concentrate ratio in complete rations using unconventional sweet sorghum bagasse (SSB), a by product of ethanol industry as sole roughage source. Eight rations were prepared with roughage to concentrate ratio of 100:0 to 30:70. Significantly (P<0.01) higher in vitro gas production volume (ml) at 24 h incubation, in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) were recorded for the rations with roughage (R) to concentrate (C) ratio of 80R:20C to 30R:70C compared to 100R:0C and 90R:10C rations. Whereas, truly digestible organic matter (TDOM) was significantly (P<0.01) higher for the rations 90R:10C to 30R:70C compared to sole SSB. Among all the rations, 30R:70C has shown highest (P<0.01) IVOMD, ME and TDOM and the trend observed in ME, TDOM values reflected that, as the concentrates proportion increased, these values were also proportionately increased. The partitioning factor (PF, mg/ml) value obtained was ranged from 2.79±0.01 to 3.18±0.01 for the experimental rations. The rations from 90R:10C to 30R:70C were significantly (P<0.01) higher in PF, microbial biomass production (MBP) and efficiency of microbial biomass production (EMBP) compared to the ration contained 100 per cent SSB. There was no significant difference observed for PF and EMBP among the rations from 60R:40C to 30R:70C, wherein the SSB proportion decreased from 60 to 30 per cent in the rations. Where as for MBP, no significant difference was observed in the rations from 50R:50C to 30R:70C. These rations have also shown higher IVOMD resulting in higher microbial biomass synthesis. The less intense microbial activity was reflected by low volumes of gas produced in the rations of sole SSB to 70R:30C. The NH3-N at 24 h of incubation was significantly (P<0.01) increased as the proportion of concentrate increased in the ration. Significantly (P<0.01) lowered total volatile fatty acid concentration was observed in the rations VII, VIII followed by V and VI. Therefore, the present study suggested that sweet sorghum bagasse (SSB) can be included in complete rations for ruminants at the level of 50-60 per cent for economic milk and meat production.